The role of phagocytosis and circadian entrainment in regulating innate immunity - Geiger, Sarah Sofia (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2017)
Lifestyles in wide parts of the world have changed. Exposure to artificial light at night, intermittent meals, night-/ shift-work is part of the everyday life for many people, leading to chronic disruption of their internal 24h timing system, the circadian clock. Only now are we beginning to understand the consequences circadian disruption may have on health and wellbeing. Obesity, cancer and incidences of other inflammatory and metabolic diseases have equally increased and association with circadian disruption has been made. Besides chronic diseases, daily rhythms in acute inflammation following an infection have been observed in mice. The integration of the immune and the circadian system has been the focus of many studies, and although much progress has been made, our understanding is still lacking. In the course of this study we investigated two aspects of daily oscillations in the immune response in mouse models.
Keywords: Biochemistry & Immunology, Ph.D.; PhD Trinity College Dublin, 2017